2009
DOI: 10.1002/btpr.318
|View full text |Cite
|
Sign up to set email alerts
|

Microparticle‐mediated gene delivery for the enhanced expression of a 19‐kDa fragment of merozoite surface protein 1 of Plasmodium falciparum

Abstract: The 19 kDa carboxyl-terminal fragment of merozoite surface protein 1 (MSP1(19)) is a major component of the invasion-inhibitory response in individual immunity to malaria. A novel ultrasonic atomization approach for the formulation of biodegradable poly(lactic-co-glycolic acid) (PLGA) microparticles of malaria DNA vaccines encoding MSP1(19) is presented here. After condensing the plasmid DNA (pDNA) molecules with a cationic polymer polyethylenimine (PEI), a 40 kHz ultrasonic atomization frequency was used to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…A number of earlier malaria vaccine studies focused on developing synthetic nanoparticles and microparticles for the delivery of parasite genes or proteins and a majority of the formulations included the biocompatible polymer poly (lactic-co-glycolic acid)—PLGA [ 129 134 ]. For the first time, iREVs from in vitro P. falciparum cultures and corresponding uninfected RBC derived EVs (uREVs), have been evaluated for their potential as natural antimalarial drug delivery systems [ 118 ].…”
Section: Malaria Prevention and Control: The Influence Of Evs In Therapeutics And Vaccine Developmentmentioning
confidence: 99%
“…A number of earlier malaria vaccine studies focused on developing synthetic nanoparticles and microparticles for the delivery of parasite genes or proteins and a majority of the formulations included the biocompatible polymer poly (lactic-co-glycolic acid)—PLGA [ 129 134 ]. For the first time, iREVs from in vitro P. falciparum cultures and corresponding uninfected RBC derived EVs (uREVs), have been evaluated for their potential as natural antimalarial drug delivery systems [ 118 ].…”
Section: Malaria Prevention and Control: The Influence Of Evs In Therapeutics And Vaccine Developmentmentioning
confidence: 99%
“…The same group subsequently reported high levels of gene expression and moderate cytotoxicity in COS-7 cells using a similar carrier with plasmid DNA encoding PyMSP1-19 formulated via ultrasonic atomization. 5 Previously, we have shown that magnetofection significantly improved the transfection efficiency of DNA encoding P. yoelii merozoite surface protein1-19 (MSP1-19) (VR1020-PyMSP1- 19) in COS-7 cells. 6 The vector compositions of superparamagnetic iron oxide nanoparticles (SPIONs) and PEI complexed under acidic condition showed better DNA transfection than at neutral condition, possibly due to the protonated structures of PEI polymer that entrapped and condensed higher amounts of DNA.…”
Section: Introductionmentioning
confidence: 99%
“…The delivery of P. vivax antigens using PLGA as a vehicle demonstrated promising and improved immune response when compared to standard vaccination technique (128). In addition, PLGA microparticles have been used to deliver Plasmodium antigenencoding plasmid DNA to antigen-presenting cells (129). Targeting the sexual stage of the parasite by transmission blocking vaccines have been shown to be promising but less efficient.…”
Section: Potential Of Evs In Malaria Vaccine Developmentmentioning
confidence: 99%